Simulating Illness: Experiencing Visual Migraine Impairments in Virtual Reality - Misztal, Sebastian; Carbonell, Guillermo; Zander, Lysann; Schild, Jonas (SeGAH ... IEEE ... International Conference on Serious Games and Applications for Health (Online), 2020)
Combining virtual reality (VR) and serious games has shown high potential to raise understanding for patients and how symptoms might impact their well-being. To investigate migraine symptoms, we developed a visual migraine simulation in a virtual environment (VE) using a VR head-mounted display (HMD). For the migraine visualization we developed a migraine aura combined with an overexposure effect. We conducted a user study (N = 32) in a within-subject design with two conditions: (1) taking the perspective of a migraine patient and only imagining to suffer from migraine, (2) experiencing migraine by additionally being exposed to a migraine visualization. Participants answered questionnaires measuring their empathic reaction towards migraine patients and their experienced presence. Results yield that participants showed a significantly and notably higher empathic reaction and a slightly stronger sense of presence when visually experiencing migraine symptoms, compared to only imagining to suffer from migraine.